Advancements in Traditional Medicine: Preparation and Characterization of Pomegranate Extract Raft Forming Tablets - S, Harshith; KP, Hemalatha; SP, Mancy; Y, Chandana (Journal of Neonatal Surgery, 2025)
The present research work aim was to formulate and evaluate Pomegranate extract raft forming tablets by Direct Compression and Wet Granulation methods. Pomegranate extract is a source of powerful polyphenols that offer potent health support for cardiovascular system. They support healthy blood flow and metabolism, help keep blood pressure within the normal range, and contribute to a balanced inflammatory response. Pectin and guar gum are gel-forming agents used at various concentrations to formulate raft-forming tablets. Upon contact with gastric fluids, they create a viscous, cohesive gel in which each portion swells and merge to form a continuous layer, known as a raft. This raft floats on the gastric fluids due to its low bulk density, which results from the generation of carbon dioxide. Thus it produces retention of dosage form which enhances gastric retention and prolongs drug delivery within the gastrointestinal tract by remaining buoyant on gastric fluids, allowing for a sustained and controlled drug release at the desired rate. The developed pomegranate raft-forming tablets were thoroughly evaluated for both pre-formulation and post-formulation parameters. FTIR and DSC analyses confirmed the compatibility of pomegranate extract with the selected excipients, indicating no significant interactions. Among all formulations tested, F12 demonstrated superior performance, exhibiting optimal raft weight, minimal buoyancy lag time and the most substantial raft formation. Notably, raft weight increased proportionally with higher concentrations of sodium alginate. Overall, formulation F12 provided the best combination of controlled drug release and floating characteristics compared to the other formulations.